THE IMPLEMENTATION OF MAKE A MATCH MODEL IN WRITING POETRY AT SENIOR HIGH SCHOOL LEVEL IN MADURA - Aini, Nor; Listyowati, Rini; Hanna, Ina Daril (Universitas Muhammadiyah Metro, 2025)
Writing poetry is often considered a difficult skill for students, thus requiring innovative learning models to increase their engagement and creativity in the classroom. The purpose of this research was to determine the implementation of Make a Match Model in writing poetry and the challenges faced by students when implementing the Make a Match Model in writing poetry. This reserach uses a case study design. participants were 22 EFL students from eleventh grade at MA Al-Djufri. The instruments used include observation, interviews, and documentation. Data were collected through classroom observations and interviews with students and teacher, then analyzed using descriptive qualitative techniques, including data reduction, data display, and conclusion drawing. The results show that the implementation of the Make a Match Model begins with the teacher preparing poetry material and cards containing questions and answers, explaining the steps of writing poetry, forming student groups, distributing the cards, matching them, writing poems, and presenting the final work. Challenges faced by students include difficulty in matching card, limited vocabulary, confusion about poetry structure, lack of self-confidence in presenting their work. The implication of this reserach is future research is suggested to examine of this model on other language skills or educational levels.